The LungVision navigational platform for peripheral lung nodule biopsy and the added value of cryobiopsy - Pertzov, Barak (Thorac Cancer, 2021)
BACKGROUND: The LungVision system is a novel augmented‐fluoroscopy‐based real‐time navigation and guidance technology for bronchoscopy that can be integrated with any standard biopsy tool, including the cryoprobe, to enable real‐time visualization and localization of pulmonary nodules. OBJECTIVES: To evaluate the diagnostic yield and safety among patients undergoing peripheral pulmonary nodule biopsy with the LungVision system. METHODS: This prospective, single‐center study was conducted at Rabin Medical Center in Israel. All patients that underwent peripheral pulmonary nodule biopsy with the LungVision system from January 2016 to August 2020 were included. All procedures were performed under moderate sedation. The primary outcome was tissue diagnosis by either identification of malignant cells or benign diagnosis. Secondary outcomes were safety and the added value of cryobiopsy. RESULTS: Sixty‐three procedures were performed during the study period. Median lesion size (interquartile range) was 25.0 mm (18–28 mm). The diagnostic yield overall was 27/33 (81.8%) and for lesions smaller than 20 mm was 13/18 (72.2%). In nine cases the transbronchial cryobiopsy showed tissue with malignant cells that were not found in any other biopsy material taken with other sampling tools. One patient was treated with a chest tube for a pneumothorax. No other major complications were reported. CONCLUSIONS: The LungVision system showed good feasibility and safety for peripheral pulmonary nodule biopsy. The system is compatible with all biopsy tools, including the cryoprobe. Randomized controlled trials are needed to accurately ascertain its diagnostic yield.